2005 IEEE/RSJ International Conference on Intelligent Robots and Systems 2005
DOI: 10.1109/iros.2005.1545341
|View full text |Cite
|
Sign up to set email alerts
|

Prosody based emotion recognition for MEXI

Abstract: Abstract-This paper describes the emotion recognition from natural speech as realized for the robot head MEXI. We use a fuzzy logic approach for analysis of prosody in natural speech. Since MEXI often communicates with well known persons but also with unknown humans, for instance at exhibitions, we realized a speaker dependent mode as well as a speaker independent mode in our prosody based emotion recognition. A key point of our approach is that it automatically selects the most significant features from a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Previous work [2] has indicated that an average emotion recognition rate of 84% is achieved in speaker-dependent experiments, whereas for the speaker-independent case the emotion recognition drops to 60%. The aforementioned conclusion is also verified in [56] for 10 different classifiers.…”
Section: Speaker-independent Experimental Protocolmentioning
confidence: 86%
“…Previous work [2] has indicated that an average emotion recognition rate of 84% is achieved in speaker-dependent experiments, whereas for the speaker-independent case the emotion recognition drops to 60%. The aforementioned conclusion is also verified in [56] for 10 different classifiers.…”
Section: Speaker-independent Experimental Protocolmentioning
confidence: 86%
“…Most of the existing systems for automatic vocal affect recognition were trained and tested on speech data that was collected by asking actors to speak prescribed utterances with certain emotions (e.g., [6] and [79]). As the utterances are isolated from the interaction context, this experimental strategy precludes finding and using correlations between the paralinguistic displays and the linguistic content, which seem to play an important role for affect recognition in daily interpersonal interactions.…”
Section: Audio-based Affect Recognitionmentioning
confidence: 99%
“…The popular features are prosodic features (e.g., pitch-related features, energy-related features, and speech rate) and spectral features (e.g., mel frequency cepstral coefficients (MFCCs) and cepstral features). Most of the existing approaches are trained and tested on speech data that were collected by asking actors to speak prescribed utterances with certain emotions [10], [13]. However, the fact 1520-9210/$26.00 © 2010 IEEE that deliberate behavior differs in audio profile and timing from spontaneous behavior has led research to shift towards the analysis of spontaneous human behavior in naturalistic audio recordings.…”
Section: Related Research and Motivationmentioning
confidence: 99%